(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1996)
Reports rescue excavation on a roughly circular, ditch-enclosed, cemetery site which uncovered a complex cluster of east/west and north/south facing burials. There were crudely worked sandstone `head-sets’ in some graves but no artefacts.